PENGEMBANGAN MODUL KIMIA PADA MATERI SISTEM PERIODIK UNSUR BERBASIS BUDAYA LITERASI - SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2021)
This study aims to determine the feasibility of a literacy culture-based chemistry module on the Elements Periodic System (SPU) material and to determine the increase in student learning outcomes. Research Methods Research and Development. The sample of the research was 12 students of the Master of Science Education Study Program, FKIP UNCEN. The results showed that the chemistry module was suitable for use as teaching material and the improvement of student learning outcomes with the n-Gain test was obtained an average of 0.81 in the high category